Student teachers’ work on instructional explanations in multiplication – representations and conversions between them - Valenta, Anita; Enge, Ole (NOMAD Nordic Studies in Mathematics Education, 2013)
In this study we are analysing student teachers’ instructional explanations. The study is based on student teachers’ written work on two different tasks about different strategies and properties in multiplication and explaining these. Our research questions concern the type of representation registers student teachers use in their explanations. In explanations where several representation registers are used, we analyse what can be challenges in conversions between representations. Data is analysed using the framework of Duval’s cognitive analysis, and analyses and discussions are related to development of mathematical knowledge for teaching.